Pesantren dan Politik Lokal:: Jejak Koalisi Moral Dalam Kontestasi Elektoral di Wajo - Besse Sri Ratih; Muhammad Al Hamid; Andi Naharuddin (Journal of Peace, Security and Democracy, 2025)
As'adiyah Islamic Boarding School and PAN cadres have a close relationship because many alumni of the boarding school are cadres. Many PAN cadres hold important positions in the Wajo Parliament and even the position of Chairman of the PAN DPP is an alumni of Asadiyah Islamic Boarding School, so indirectly it will be easier to establish communication with alumni and students of Asadiyah who are members of PAN. PAN uses a political strategy by introducing students to actors according to religious teachings and conditions in Wajo. Through religious activities, PAN maintains relations with the boarding school, sometimes with financial and infrastructure support. In addition, the success of alumni students, and the position of actors with PAN containers labeled as religion is very profitable and is an extraordinary strategy that is not intentional. Through religious programs such as religious studies, preaching, and Friday sermons and other activities, it seems to be a strong communication and branding pattern and in line with PAN's position which is engaged in the religious field with the keywords "branding Actor is a preacher, and branding communication entitled silaturahmi". The condition of Wajo as a city of Santri, PAN's position with a religious orientation, and the elected regent with a Muhammadiyah background who is supported by PAN's campaign team cadres who are alumni of the Asadiyah Islamic Boarding School, this is the right strategy in terms of winning the hearts of voters and shifting the incumbent's seat.